VEGETABLE OIL AS A BASE FOR LUBRICANTS: CURRENT CHALLENGES AND FUTURE PERSPECTIVES - HETMAN, MYKHAILO (Herald of Khmelnytskyi National University. Technical sciences, 2025)
Lubricants play a critical role in ensuring the reliable and efficient operation of equipment across a wide range of industrial sectors. By reducing friction, wear, and overheating, lubricants contribute significantly to the longevity and performance of mechanical components. The absence of proper lubrication or the use of unsuitable lubricants often results in premature equipment failure, leading to substantial financial losses due to downtime, repairs, or replacement of machinery. Traditionally, mineral oils derived from petroleum have been used as the base for lubricants. However, their use is increasingly associated with environmental hazards—approximately 30% of lubricants consumed end up being released into the environment, contaminating soil and water bodies, and threatening ecosystems. With the ongoing depletion of non-renewable mineral resources and growing awareness of environmental concerns, there is an urgent need to find more sustainable and eco-friendly alternatives. One of the most promising directions is the use of vegetable oils as a base for lubricants. Vegetable oils are renewable, biodegradable, and exhibit excellent lubricating properties, a high viscosity index, and reduced environmental impact compared to traditional mineral oils. Despite these advantages, several challenges hinder the widespread adoption of vegetable-based lubricants. Key drawbacks include low oxidative and hydrolytic stability, relatively high production costs, competition with the food industry, sensitivity of tribological properties to temperature changes, and poor performance at low temperatures. Current scientific research aims to address these limitations through various strategies such as using non-edible oil sources, incorporating functional additives, and applying chemical or thermal modification techniques to enhance oil stability and performance. For broader industrial adoption, continued research and development are essential, alongside regulatory support and environmental policy incentives aimed at promoting sustainable lubricant technologies.
Keywords: vegetable oil; biolubricant; mineral lubricant; lubricating properties